The RNA polymerase III terminator used by a B1-Alu element can modulate 3' processing of the intermediate RNA product. - Maraia, R J (1992)
The dispersion of short interspersed elements (SINEs) probably occurred through an RNA intermediate. B1 is a murine homolog of the human SINE Alu; these elements are composed of 5' G + C-rich regions juxtaposed to A-rich tracts and are flanked by direct repeats. Internal promoters direct RNA polymerase III to transcribe B1 and Alu elements and proceed into the 3' flanking DNA until it reaches a (dT)4 termination signal. The resulting transcripts contain 3'-terminal oligo(U) tracts which can presumably base pair with the A-rich tract to form self-primed templates for reverse transcriptase and retrotransposition. Nuclear extracts from mouse tissue culture cells contain an RNA processing activity that removes the A-rich and 3'-terminal regions from purified B1 RNAs (R. Maraia, Nucleic Acids Res. 19:5695-5702, 1991). In this study, we examined transcription and RNA processing in these nuclear extracts. In contrast to results with use of purified RNA, nascent transcripts synthesized in nuclear extract by RNA polymerase III are not processed, suggesting that the transposition-intermediate-like RNA is shielded from processing by a protein(s). Alteration of an AATTTT TAA termination signal to a GCTTTTGC signal activated processing by greater than 100-fold in coupled transcription/processing reactions. A similar difference was found when expression was compared in frog oocytes. No difference in processing was found if the transcripts were made by T7 RNA polymerase in the presence of the nuclear extract, indicating that the different processing effects of the two terminators were dependent on synthesis by polymerase III. The modulation of processing of B1-Alu transcripts and the potential for retrotransposition of B1 and Alu DNA sequences are discussed.